Pandemi Covid-19 Serta Pengaruhnya Terhadap Aktivitas Ibadah Dan Nilai-Nilai Al Islam Kemuhammadiyahan - Firman Noor Hasan (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2021)
During the Covid-19 pandemic, the government implemented WFH (Work From Home), LFH (Learn From Home), and PFH (Pray From Home), so as to have a changing impact on human behavior both in terms of economy, quality of worship, learning, and others. This study aims to determine the worship activities carried out by respondents and their relationship to their practice of Al-Islamic Kemuhammadiyahan values in their daily lives in the midst of the COVID-19 pandemic. The results of the research obtained from 87 respondents indicated that the religious activities and activities of practicing the Islamic values of Kemuhammadiyahan that were carried out by respondents in the midst of the COVID-19 pandemic situation, actually decreased and also greatly influenced the decrease in the practice of the Islamic values of Kemuhammadiyahan. This is also influenced by other variables that were not included in this study, such as appeals and regulations from the Regional Government / Pemprov regarding PSBB (Large-Scale Social Restrictions), as well as recommendations from the Central Government to reduce activities & activities outside the home such as work, study, crowds, and others.